2022
DOI: 10.1136/openhrt-2022-002035
|View full text |Cite
|
Sign up to set email alerts
|

Elevated cardiovascular disease risk in low-income women with a history of pregnancy loss

Abstract: ObjectivePregnancy is associated with elevated risk of cardiovascular diseases (CVD), but little is known regarding the association between CVD and specific types of pregnancy losses. The aim of this study is to investigate the effects of pregnancy loss on the risk of subsequent CVD of any type.MethodsThis prospective longitudinal study examines medical records between 1999 and 2014 for Medicaid beneficiaries born after 1982 who lived in a state that funds all reproductive health services, including induced ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Recent research using a large low-income American population also adds to the weight of evidence linking abortion to cardiovascular outcomes. 48 After adjusting for multiple confounders, women whose first pregnancy ended in either miscarriage or abortion were 18% more likely to develop CVD and more likely to have a haemorrhagic stroke compared with women with only live births. Unfortunately, the American study ( n = 1 157 980) did not segregate the results associated with miscarriage and abortion separately.…”
Section: Discussionmentioning
confidence: 95%
“…Recent research using a large low-income American population also adds to the weight of evidence linking abortion to cardiovascular outcomes. 48 After adjusting for multiple confounders, women whose first pregnancy ended in either miscarriage or abortion were 18% more likely to develop CVD and more likely to have a haemorrhagic stroke compared with women with only live births. Unfortunately, the American study ( n = 1 157 980) did not segregate the results associated with miscarriage and abortion separately.…”
Section: Discussionmentioning
confidence: 95%
“…First, we have considered the complete reproduction of a woman in our analyses; however, we were not able to address fully the issue of pregnancy loss in relation to CVD death. Previous studies reported that pregnancy loss (miscarriage, stillbirth, and abortion) is a risk factor for CVD and early mortality [ 10 , 11 ]. However, when we analyzed our data restricted to mothers who had no lifetime perinatal loss, the results were similar to the main analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Women with a history of pregnancy loss have a greater risk of CVD [ 10 ] and premature mortality up to three decades later, particularly cardiovascular, cancer, and suicide-related deaths [ 11 ]. Systematic review and meta-analyses also reported that the risk of CVD was higher among women with prior pregnancy loss (miscarriage, stillbirth, and induced abortion) [ 12 ] and pregnancy loss associated mortality is more than double that of delivery associated mortality [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A history of pregnancy loss (PL), whether induced or naturally occurring, has been associated with a higher risk of subsequent metabolic disorders, including cardiovascular disease ( 15 , 16 ), premature mortality ( 17 ), type 2 diabetes ( 18 , 19 ) and atherosclerotic disease ( 20 ), especially when there is recurrent PL. Moreover, a prospective longitudinal study revealed an important temporal relationship that a delayed and more prolonged increased risk of CVD is associated with a first pregnancy loss ( 21 ). However, to the best of our knowledge, the early-term effects of PL on gestational cardiovascular health remain uncertain.…”
Section: Introductionmentioning
confidence: 99%